Justice Not for Sale: A Constitutional Defense of the Missouri Plan for Judicial Selection - Cort A. Van Ostran (Washington University Journal of Law & Policy, 2014)
Judicial selection for state courts in the United States has become a controversial subject in American jurisprudence. In the past several decades, a debate has emerged over the proper balance between independence and accountability in the judicial selection process. Professor Nelson Lund entered this debate by arguing that merit-based judicial selection plans—those plans that utilize nonpartisan commissions in judicial appointments (and therefore fall outside either a traditional appointment or electoral scheme)—violate the Equal Protection Clause of the Constitution because of the enhanced role attorneys play in the process, resulting in what Professor Lund describes as the disenfranchisement of non-attorney voters. This Note argues that Lund’s criticism is erroneous; rather, merit-based judicial selection plans do not violate the Equal Protection Clause because they promote, rather than discourage, equal participation within a tradition of non-electoral schemes that have been accepted by the United States Supreme Court for certain bureaucratic offices. This Note argues for the constitutionality of merit-based plans on both their consistence with previously legitimated non-electoral processes and their promotion of democratic participation.
Keywords: judicial selection; Missouri Plan; non-electoral; elective judicial selection; appointive judicial selection; merit-based judicial selection; Dool v. Burke; Kales Plan; nominating commission; Salyer/Ball exception; one person one vote; Nelson Lund